The Problem of Risk-Related Return of Investments and the Possibility of its Solution - Jasienė, Meilė; Kočiūnaitė, Diana (Ekonomika, 2007)
With the growth of economy increases also interest in financial markets and the possibilities they offer, and larger part of society take part in investment activities. Although investments differ according to their instruments, strategies, areas, terms and other indications, usually most important to the investor is the return of investment and its risk. When the investor undertakes big risk, usually he expects also a better yield or return, but the additional risk can present a different growth of return. One of the most popular ways of investment in Lithuania are pension funds, which also differ according to their strategies of investment, return to the investor and the risk undertaken. It should be noted that the strategy of investment alone does not allow to determine and evaluate unambiguously the level of return and risk.The aim of the article was to try to present a method of the evaluation of investment return according to the level of the risk, using the Sharpe ratio, and on this ground to analyse the return of the Lithuanian pension funds of the second stage for one conditional unit of the fund risk.The yield of investment is determined as the annual percentage rate calculated by dividing annual return by the amount of investment, or the rate of return. Many factors influence the yield of investments and their return. Among them are various types of risk, which are reflected one way or another as a component in their quantitative expression. The yield theoretically can be divided particularly into the components determined by the mentioned factors; their quantitative evaluation can be very complicated and sometimes impossible. According to the aim of the present research, we will examine return as the sum of two components, i.e. addition to the return of riskfree investment and risk.The effectiveness of an investment can be evaluated by comparing the addition to the risk of investment return with the risk. The Sharpe ratio was used to make this analysis which shows the number of units of investment return per unit of the risk of investment.Methods used by the Lithuanian pension funds managing companies and the institutions supervising the pension funds are analysed. These methods are used to calculate the results of the second stage pension funds and to evaluate their possibilities.The method presented in the article uses methods of statistical analysis, yield analysis, and the Sharpe ratio, which is different from the methods used by pension fund managing companies and supervision institutions, and which offers the possibility to analyse the effectiveness of the second stage pension fund and to evaluate the capability of the pension funds managing companies to invest with profitable results according to the level of risk. This method allows to compare pension funds of different investment strategies and to choose those that work most successfully according to the best relationship between return and risk.As the analysis showed, the numbers of the Sharpe ratio of one third of the second stage funds are negative because of a small annual return of pension funds and rather big taxes of asset management. The other pension funds, in which the mentioned ratios are positive, not all work effectively. The risk of some pension funds, to compare with the return, is too big.The method presented in the paper - allows comparing second stage pension funds with other alternatives of long·term investment, such as pension funds of additional voluntary accumulation (of the third stage) and investment funds.